Antibody-drug conjugates targeting CD248 inhibits liver fibrosis through specific killing on myofibroblasts - Shaojie Liu; Donghui Han; Chao Xu; Fa Yang; Yu Li; Keying Zhang; Xiaolong Zhao; Jiayu Zhang; Tong Lu; Shiqi Lu; Changhong Shi; Rui Zhang; et al. (BMC, 2022)
Abstract Background Chronic liver injury induces pathological repair, resulting in fibrosis, during which hepatic stellate cells (HSCs) are activated and transform into myofibroblasts. CD248 is mainly expressed on myofibroblasts and was considered as a promising target to treat fibrosis. The primary aim of this study was to generate a CD248 specific antibody-drug conjugate (ADC) and evaluate its therapeutic efficacy for liver fibrosis and its safety in vivo. Methods CD248 expression was examined in patients with liver cirrhosis and in mice with CCl4-induced liver fibrosis. The ADC IgG78-DM1, which targets CD248, was prepared and its bioactivity on activated primary HSCs was studied. The anti-fibrotic effects of IgG78-DM1 on liver fibrosis were evaluated in CCl4-induced mice. The reproductive safety and biosafety of IgG78-DM1 were also evaluated in vivo. Results CD248 expression was upregulated in patients with liver cirrhosis and in CCl4-induced mice, and was mainly expressed on alpha smooth muscle actin (α-SMA)+ myofibroblasts. IgG78-DM1 was successfully generated, which could effectively bind with and kill CD248+ activated HSCs in vitro and inhibit liver fibrosis in vivo. In addition, IgG78-DM1 was demonstrated to have qualified biosafety and reproductive safety in vivo. Conclusions Our study demonstrated that CD248 could be an ideal target for myofibroblasts in liver fibrosis, and CD248-targeting IgG78-DM1 had excellent anti-fibrotic effects in mice with liver fibrosis. Our study provided a novel strategy to treat liver fibrosis and expanded the application of ADCs beyond tumors. Graphic Abstract